Japan's embryo transfer technology and its feasibility in hastening livestock improvement in Southeast Asia - H. Kanagawa; O. Abas Mazni; C.A Valdez (Hemera Zoa, 1988)
In Japan, progress has been achieved in the development of embryo transfer (ET) technology in the last few years. Research on the other related technologies such as cryopreservation, in vitro fertilization, embryo manipulation and sexing are actively being carried out. However, its practical application is still limiteed. It is now being used for rapid proliferation of desirable dairy and beef cattle. About 100 organizations are involved in ET practice and research. The number of ET trained technicians has also increased. However, ET is still a relatively expensive technique which great effort and financial risk.